On the credibility of QS and THE ranking by subject area: misalignment of subject mapping to academic disciplines - Alshraideh, Hussam; Abdelgawad, Mohamed (Scientometrics, 2025)
In this study, we point the attention to some inaccuracies in the mapping between the journal subject classification by Elsevier and the narrow subject field used by QS (Quacquarelli Symonds) and THE (Times Higher Education) in their World University Rankings by subject. We noticed that inaccuracies in this mapping will result in classifying some publications under far disciplines, rendering the announced subject ranking inaccurate. To give an example of these inaccuracies, publications on fuel technology, nuclear engineering, and all energy-related studies are classified under Civil Engineering in THE ranking and under Electrical and Electronics Engineering under the QS ranking. This is completely unfair as many of these studies are conducted by researchers in Mechanical or Chemical engineering disciplines. To demonstrate the effect of this erroneous mapping on the final ranking, we obtained the publications data for 13 institutions from the top 20 institutions in the Arab World from 2017 to 021 and their citations until mid-2022 as indexed in Scopus. Following QS and THE subject ranking methodology, we then re-ranked these institutions based on citations per paper and h-index indicators based on a modified subject mapping suggested by a sample of 12 faculty members from 6 different engineering departments at the authors’ institution. We found that the new ranking differed considerably from the one calculated by QS and THE based on their controversial subject mapping. Many institutions (sometimes 10 out of 13) had their rank change in some subject areas with the rank of some institutions dropping 6 ranks out of 13 in some cases! We believe this study sheds light on the inaccuracies in subject rankings and the importance of coming up with a unified subject mapping to be used by the different ranking bodies.